Mathematical Modeling in Biomedical Imaging I Electrical and Ultrasound Tomographies, Anomaly Detection, and Brain Imaging - Ammari, Habib (Mathematical Biosciences Subseries, 2009)
This volume gives an introduction to a fascinating research area to applied mathematicians. It is devoted to providing the exposition of promising analytical and numerical techniques for solving challenging biomedical imaging problems, which trigger the investigation of interesting issues in various branches of mathematics.